Relapse after Orthodontic-Surgical Treatment: A Retrospective Longitudinal Study - Matos, João (2023)
Long-term stability is a crucial point in order to keep the patient’s aesthetic and functional balance. The aim of this study was to evaluate dental and skeletal relapse in patients who underwent orthodontic-surgical treatment. This retrospective study included 25 patients who corrected their dentofacial deformity through orthodontics and orthognathic surgery. The dental casts and lateral cephalograms were evaluated prior to orthodontic treatment (T0), final of orthodontic-surgical treatment (T1) and long-term retention phase (T2). The Wilcoxon test with p-value corrected by the Benjamini–Hochberg method was used to assess differences between the groups. The influence of retention duration was assessed using the Kruskal–Wallis method. The association of nominal variables and differences between quantitative variables were assessed using the Fisher and Mann– Whitney tests, respectively. No dental or skeletal variable presented statistically significant differences between the final orthodontic-surgical treatment and the long-term retention phase. Eight patients presented dental relapse (32–95% CI [12.4%; 51.7%]), but no skeletal relapse was observed in any of the 25 individuals. The type of malocclusion did not influence the relapse rate of orthodontic-surgical treatment (Fisher, p = 0.202). No differences were found between the different retention times, sex and age at the end of treatment. Orthodontic-surgical treatment showed long-term stability in the present study group.